Analisis Kebutuhan Electronic Medical Record (EMR) Pasien Rawat Jalan Dewasa Menggunakan Metode UCD di RSCM - Evi Novitasari; Maya Weka Santi; Atma Deharja (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
RSUPN Dr. Cipto Mangunkusumo is a government hospital in Central Jakarta, Indonesia. The hospital hasnot used an electronic medical record with a land area of 12,1409 hectares and is still using manualmedical records, causing the length of documents to be distributed to each unit that needs it. Besides thedistance traveled causes the loss of files in it. The target achievement of medical record response time isstill very far from what has been set, which is equal to 90% of medical records reaching poly at <25minutes. Implementation of electronic medical records at RSUPN Dr. Cipto Mangunkusumo has not beenimplemented yet because the needs of the implementation of electronic medical records have not beenmet, so it is necessary to analyze the electronic medical records needs of adult outpatients. The researchmethod used is the user centered design method which is a design method that puts the user at the centerof a system design process. The process in the UCD method is to understand and determine the user'scontext, determine the needs of users and organizations, design solutions produced, and designevaluation of user needs. The results of the study are end-users of electronic medical records of adultoutpatients, namely doctors, nurses, medical recorders, and pharmacists. There are 3 needs for users andorganizations namely information needs, functional needs and non-functional needs. There are 13interface designs and interface design evaluation results, namely the design produced according to userneeds